2011
DOI: 10.1111/j.1399-3038.2010.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Mite component–specific IgE repertoire and phenotypes of allergic disease in childhood: The tropical perspective

Abstract: Sensitization to perennial aeroallergens correlates with the risk of persistent asthma (AS) in children. In tropical Singapore, multiple codominant species of mites abound in the indoor environment, and preferential species-specific sensitization has been associated with different phenotypes of allergic disease. We investigated the pattern of mite component-specific IgE (mcsIgE) in children with different phenotypes of clinical allergic disease in an environment with multiple mite species exposure. A prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
107
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 36 publications
14
107
6
Order By: Relevance
“…All of the patient sera were preadsorbed with 5 mg/ml of GST protein before use. The sera used in this study were prescreened for IgE responses to Blo t 21 in our previous study (7). Wild-type Blo t 21, GST, and mutant proteins were diluted in PBS to 20 g/ml.…”
Section: Expression and Purification Of Recombinant Blo T 21-mod-mentioning
confidence: 99%
See 4 more Smart Citations
“…All of the patient sera were preadsorbed with 5 mg/ml of GST protein before use. The sera used in this study were prescreened for IgE responses to Blo t 21 in our previous study (7). Wild-type Blo t 21, GST, and mutant proteins were diluted in PBS to 20 g/ml.…”
Section: Expression and Purification Of Recombinant Blo T 21-mod-mentioning
confidence: 99%
“…Blo t 21 is able to elicit a positive allergic response in 57.9% (286 of 494) of atopic patients attending outpatient allergy clinics over 1.5 years (5). Following this, the patterns of mite component-specific IgE were investigated in a total of 253 atopic children (7). The results revealed that the most common mite allergens recognized were Der p 2 (71%), Der p 1 (64%), Blo t 21 (56%), Blo t 5 (45%), and Blo t 7 (44%) (7).…”
mentioning
confidence: 99%
See 3 more Smart Citations